TP53 mutations are associated with very complex karyotype and suggest poor prognosis in newly diagnosed myelodysplastic syndrome patients with monosomal karyotype. Issue 3 (7th February 2020) - Ren, Yanling; Wang, Jinghan; Zhang, Hua; Mei, Chen; Ye, Li; Luo, Yingwan; Zhou, Xinping; Zhu, Shuanghong; Jiang, Lingxu; Wang, Lu; Jin, Jie; Tong, Hongyan
Abstract: Aim: The aim of this study was to evaluate the clinical and molecular characteristics of myelodysplastic syndrome (MDS) patients with monosomal karyotype (MK). Methods: Eighty MDS patients with MK diagnosed between January 2010 and December 2018 were included in the retrospective study. Seventy‐three had complex karyotype (CK) and 46 had very CK (vCK, ≥ 5 abnormalities). Clinical information was collected, and a panel of 37 genes, on which mutations have been previously reported to be associated with MDS patients, was analyzed by next‐generation sequencing. Genetic and biological features and their association with survival were evaluated. Results: Monosomy 5, 7, and 17 were the most frequent and mainly occurred in patients with vCK. While median overall survival (OS) for all patients was 12.8 months with 95% CI 9.1‐16.5, patients with vCK had shorter OS (8.4 months with 95% CI 3.9‐12.8) than those with non‐vCK (16.1 months with 95% CI 11.5‐20.8) ( P = .02). At least one gene mutation was detected in 76 patients (95%), TP53 mutations were detected in 57 patients, and their median OS was significantly shorter than those without TP53 mutations (9.5 months with 95% CI 7.5‐11.5 vs 26.1 months with 95% CI 8.0‐44.2, P < .01). In 34 patients who received treatment with decitabine, 25 with TP53 mutations had higher overall response rate than those with wild‐type TP53 (60% vs 22.2%, P = .03). However, OS was still significantly shorter in those with TP53 mutations (10.1 vs 26.1 months, P = .03). Multivariate analysis confirmed that TP53 mutations was an independent poor prognostic factor on OS. Conclusions: CK and vCK overlap in most of the MDS patients with MK. TP53 mutations occur more frequently in MDS patients with vCK, and both TP53 mutations and vCK are adverse prognostic factors.